Paradigms, Strategies, and Challenges of Quality Control in Higher Education in the Digital Era: A Systematic Literature Review - Giovani Septio; R Madhakomala (Dinasti International Journal of Education Management and Social Science, 2025)
Digital transformation demands systemic adaptation in the quality assurance framework for higher education. This study aims to synthesize literature on the paradigms, strategies, and challenges of quality control in the digital era using a Systematic Literature Review (SLR) guided by PRISMA. Thematic analysis was conducted on 39 selected articles from an initial corpus of 80. The main findings show a paradigm evolution towards the "Quality 4.0" concept, which is proactive and data-driven. Successful implementation requires a multidimensional strategy encompassing transformational leadership, integrated technology infrastructure, human resource capacity development, curriculum design, and accreditation transformation. However, this process faces significant technological, organizational, pedagogical, and regulatory challenges. It is concluded that digital quality control is a holistic transformation that transcends technology adoption, demanding fundamental changes in culture and processes. Synergy between adaptive institutional policies and flexible regulatory support is necessary to realize innovative and high-quality higher education.